Improving the biodegradability of rice straw by electrochemical pretreatment - Sun, Shaohua; Zhang, Yuanyuan; Yang, Zhaoyang; Liu, Chunmei; Zuo, Xiaoyu; Tang, Yang; Wan, Pingyu; Liu, Yanping; Li, Xiujin; Coulon, Frederic; Hu, Qing; Yang, Xiao Jin (Elsevier, 2022)
The efficacy of NaOH, alkaline hydrogen peroxide (NaOH-H2O2), electrochemically produced NaOH-H2O2 (eNaOH-H2O2) and electrohydrolysis (EH) pretreatments was investigated for anaerobic digestion of rice straw. The cumulative biogas production was enhanced by 8%, 22% and 14% in the NaOH-H2O2, eNaOH-H2O2 and EH relative to conventional NaOH pretreatment. The chemical and electrochemical pretreatments decreased the crystallinity of cellulose and created a porous surface vein. Electrochemical NaOH-H2O2 pretreatment is efficient to promote microbial degradation of lignocellulose for biogas production while the risks associated with the transportation and storage of H2O2 are avoided. EH reduces the pretreatment time significantly and is a promising approach for utilizing rice straw biomass to produce renewable energy.
Keywords: Rice straw; Pretreatment; Anaerobic digestion; Electrohydrolysis; Electrolytic peroxide